Detecting of bonding defects using an SHM fiber-optics distributed sensors system in typical wing spar coupon - Pellone, L.; Ciminello, M.; Galasso, B.; Mercurio, U.; Apuleo, G.; Cozzolino, A.; Concilio, A. (AIP conference proceedings, 2020)
The use of adhesive bonding in the aeronautical structures has become a big challenge for the industries because it would allow obtaining savings in terms of cost of manufacture and weight of the structures themselves. On the other hand, relating to the certification processes, the authorities allow the use of bonded main structures as long as there is the possibility of monitoring them with reliable tools that permit verifying the strength of each bonded joint. In that framework of OPTICOMS project, funded within the European Program Clean Sky 2, an activity was carried out on a representative composite structural coupon, typical of a wing spar element, to test and setup a technology based on FBO coupled to an algorithm developed at CIRA, in perspective of more extensive campaigns on full-size components. The aim of this paper is to give a preliminary overview the performance of this SHM algorithm, based on Fiber-Optic distributed sensors system, in detecting integrity discontinuities in the bonding line of a small thin-walled beam section. The experimental tests have been arranged so to analyze the structural behavior with and without damage, and evaluate the data collected by distributed fiber optics and elaborated by the SHM algorithm.